Efficacy of Nanoparticle-based Localized Immunomodulation to Reduce Graft-versus-host Disease in Bone Marrow Transplantation: A Systematic Review - Farwa Saleem; Eisha Jabbar (Students' Supplement of Journal of Rawalpindi Medical College, 2025)
Background and Aim Graft-versus-host disease (GVHD) is a serious, life-threatening complication following bone marrow transplantation (BMT) that terribly increases transplant-related mortality and morbidity. Despite being common, conventional immunosuppression frequently results in unsatisfactory disease control and more importantly are associated with systemic toxicity and infection. Nanoparticle (NP) -based therapeutics while been explored in solid organ transplantation, remains under investigated in BMT. This study aims to compare the effectiveness of traditional immunosuppression with NP based localized treatment in GVHD mitigation in standard murine models. Methods Database search was carried out via PubMed, Science Direct, and Springer using a restriction of standard strain and the following keywords: (bone marrow transplantation OR hematopoietic stem cell transplantation) AND graft vs host disease AND nanoparticles. Search was conducted from 2000 to 2025. From the 66 studies retrieved, 15 were selected and included in this research. Based on PRISMA criteria, this review included peer-reviewed English studies using standard murine models (e.g., C57BL/6, BALB/c) undergoing allogeneic BMT with experimentally induced GVHD. Studies used IV or IP nanoparticle delivery (e.g., immunosuppressants, biopolymers) with appropriate comparators; exclusions included non-murine models, oral/subcutaneous routes, combination therapies, and non-primary literature. Data on study design, animal models, interventions, and outcomes were extracted from full texts and supplements into a structured Excel sheet. Discrepancies were resolved through discussion with a third reviewer. Risk of biased assessment was also done using SYRCLE tool. Results Murine models received different types of NPs treatment: Fullerol NPs, Bilirubin NPs, Fe₃O₄ Magnetic NPs, Carbon Nanotubes and Nanoencapsulation of T Cells. Studies indicated significantly reduced GVHD clinical scores (n=5), improved survival (n=4), and alleviation of inflammatory processes (n=4) compared to controls. Not all studies outperformed conventional immunosuppression. Surprisingly, noteworthy secondary outcome made this planned one-to-one analysis, two-dimensional by getting the Graft-versus-Leukemia (GVL) activity preserved without compromising the GVHD mitigation (n=2). No adverse effects were reported in all studies. Conclusion NPs therapy, in BMT seems to have a potential for managing GVHD effectively and more precisely compared to traditional immunosuppression. It underscores the need for in-depth translational studies. Key-Words Bone Marrow Transplantation OR Hematopoietic Stem Cell Transplantation AND Graft vs Host Disease AND Nanoparticles